Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1055/s-0040-1713399
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Wrist Radiographs in Patients with and without a Ganglion Cyst

Abstract: Objectives The purpose of this study was to find out if carpal instability played a role in the etiology of ganglion cysts. Materials and Methods Dynamic wrist radiographs of 33 patients with and without a ganglion cyst of the wrist were compared. The control group consisted of patients who had dynamic radiographs of both wrists after a traumatic event in one wrist. Measurements were performed on the contralateral uninjured side. Radiological parameters that may indicate carpal instability included: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…1 Previous reports on the relationship between wrist pain and an increased angle of the capitolunate joint are consistent with the results of our pain group. Beuckelaers and Hollevoet 5 reported that the angle of the capitolunate joint of the wrist with ganglion, one of the pathologies associated with dorsal wrist pain, was increased compared with that of the control group. In gymnasts with wrist pain evaluated with necrosis of the capitate, the articular surface of the capitate to the lunate was irregular and the capitolunate joint was enlarged.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous reports on the relationship between wrist pain and an increased angle of the capitolunate joint are consistent with the results of our pain group. Beuckelaers and Hollevoet 5 reported that the angle of the capitolunate joint of the wrist with ganglion, one of the pathologies associated with dorsal wrist pain, was increased compared with that of the control group. In gymnasts with wrist pain evaluated with necrosis of the capitate, the articular surface of the capitate to the lunate was irregular and the capitolunate joint was enlarged.…”
Section: Discussionmentioning
confidence: 99%